Relevansi Penerapan ESG Bagi Perusahaan : Systematic Literature Review - Ni Made Ayu Dwijayanti; Robith Hudaya; Tiara Kusuma Dewi; Luh Putu Lusi Setyandarini Surya (Owner : Riset dan Jurnal Akuntansi, 2025)
ESG refers to three central factors of measuring the impact of sustainability and ethics in investment decision making. The three factors are: Environmental, Social and Governance. This study is a literature study with a descriptive qualitative research type with a literature review (library research) that attempts to describe ESG in relation to company value. In this study the author uses written sources, both articles and journals that are relevant to the study in this study. The data collection technique uses the Publish or Perish (PoP) application which searches the Scopus database. In the Vosviewer software, there are 3 visualization displays in bibliometric analysis, namely ESG, Firm Value and ESG Disclosure. This application is used to see the development of research in the field of Environmental Social Governance (ESG) and a literature review to understand how ESG principles are applied to companies. A number of impacts in the implementation of ESG and its influence on company value. The implications of this research are expected to provide input for ESG-Based Policy Development, which can be used by the government to formulate policies that are more responsive to environmental, social, and governance issues. By understanding the importance of ESG, the government can attract more investments that focus on sustainability, which in turn can increase growth. Despite the challenges faced, the implementation of ESG principles in accounting practices also provides a number of benefits for companies.